2018
DOI: 10.1177/1120700018773401
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic dynamometry and gait analysis reveal different hip joint status in patients with hip dysplasia

Abstract: Although dysplasia patients have weaker hip flexion and abductor muscles than controls, their abductor muscles are sufficiently strong to ensure normal function during gait. Hence, gait analysis alone might not reveal the true, subnormal hip joint status in dysplasia patients. We suggest that comprehensive assessment of hip joint function in dysplasia patients should include more strenuous activities than gait, particularly in young(er) patients who are likely to prefer a more active lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…[15][16][17] We also found that patients with DDH experienced problems during walking, sitting, sleeping and other vital functions of everyday life. In line with our study, other studies have found that DDH is associated with gait impairments, 34 muscle strength deficits, 35 reduced function in daily living 4 and poor sleep quality. 19 36 Additionally, other studies have reported frequent traits of anxiety and depression in patients with DDH.…”
Section: Discussionsupporting
confidence: 93%
“…[15][16][17] We also found that patients with DDH experienced problems during walking, sitting, sleeping and other vital functions of everyday life. In line with our study, other studies have found that DDH is associated with gait impairments, 34 muscle strength deficits, 35 reduced function in daily living 4 and poor sleep quality. 19 36 Additionally, other studies have reported frequent traits of anxiety and depression in patients with DDH.…”
Section: Discussionsupporting
confidence: 93%
“…Walking ability and hip abduction strength were signi cantly lesser in DDH compared to FAIS patients. Consistent with our ndings, hip abduction strength decrements are well documented for DDH 9,10,31 . Between-group differences in scores for UCLA Activity, HOS ADL, SF-12…”
Section: Discussionsupporting
confidence: 92%
“…While fatty infiltration can increase in pathological conditions, the presence of abnormal fatty content in patients with DDH is not known. Mechanical muscle function, such as the ability to generate torque may be compromised in patients with DDH due to decreased muscle moment arms, 21 or other factors, but few studies of function have included patients with DDH before osteoarthritis or compared them to healthy controls 7,22 . Ultimately, alterations to muscle geometry and function, and how they relate to skeletal deformities have not been clearly presented in a single group of patients with DDH.…”
Section: Introductionmentioning
confidence: 99%